Learning Humanist Islamic Religious Education For Children With Special Needs (Case Study at SLB Negeri Wiradesa Pekalongan) - Setianto*, Gigih; Risdiani, Risdiani (Universitas Syiah Kuala, 2024)
This study aims to find out how the implementation of Humanist Islamic Education learning for children with special needs in SLB Negeri Wiradesa Pekalongan. This research is qualitative research. The results of this study show that PAI learning planning at SLB Negeri Wiradesa Pekalongan is carried out by taking into account the individual needs of students. Then the implementation of PAI learning emphasizes an individual approach that respects the uniqueness of each student. Learning evaluation is carried out according to the disabilities and abilities of students, this evaluation includes cognitive, affective, and psychomotor components, and focuses on practical application in everyday life. There are several obstacles in learning PAI at SLB Negeri Wiradesa Pekalongan, such as the shortage of teachers with special education specialties, the limited curriculum specifically designed for PAI in SLB, and the lack of availability of religious books suitable for students with special needs. This shows the need for better resources and planning to support the success of the humanist approach in PAI learning at SLB Negeri Wiradesa